IMPROVING READING ABILITY AND IDENTIFYING DRAMA ELEMENTS USING THE DISCUSSION METHOD - W Warsiman; Kamal Yusuf (Universitas Brawijaya, 2021)
The learning of drama appreciation that has been carried out by the teacher needs to be reviewed. The use of traditional methods has an impact on blocking student activity and creativity. This study aims to improve students' reading skills and identify elements of drama through the discussion method. This research was conducted for approximately two months at SDN Kepohkidul I Kecamatan Kedungadem Kabupaten Bojonegoro. The research model used was CAR (class action research). The data obtained were processed quantitatively. The results obtained indicate that the students' ability to read and identify elements of drama increased. This increase can be seen from the results of the student's absorption rate in cycle I reached 42% and in cycle II increased to 94%. The mean score of student tests in the first cycle was 66.3 and in the second cycle increased to 75.6. Based on these results, it is concluded that learning through the discussion method can improve the ability to reading and identify elements of drama in grade VI SDN Kepohkidul I kecamatan Kedungadem kabupaten Bojonegoro.